Impact of technology uptake on an Australian electricity distribution network. (July 2015) - Boulaire, Fanny; Utting, Mark; Drogemuller, Robin
Abstract: This paper presents simulation results for future electricity grids using an agent-based model developed with MODAM (MODular Agent-based Model). MODAM is introduced and its use demonstrated through four simulations based on a scenario that expects a rise of on-site renewable generators and electric vehicles (EV) usage. The simulations were run over many years, for two areas in Townsville, Australia, capturing variability in space of the technology uptake, and for two charging methods for EV, capturing people's behaviours and their impact on the time of the peak load. Impact analyses of these technologies were performed over the areas, down to the distribution transformer level, where greater variability of their contribution to the assets peak load was observed. The MODAM models can be used for different purposes such as impact of renewables on grid sizing, or on greenhouse gas emissions. The insights gained from using MODAM for technology assessment are discussed. Highlights: A compositional agent-based model was developed using the MODAM framework. Four simulations were run with a rise of photovoltaics and electric vehicles. Impact of these technologies over large areas varied up to 10%. Some transformers increase up to 85% in their peak due to EV charging. MODAM models are versatile and flexible; allowing mix-and-match of agents.